Atomic scale nanoelectronics for quantum neuromorphic devices: comparing different materials. (2016) - Prati, Enrico
This paper analyses the advancements of atomic scale nanoelectronics towards quantum neuromorphics. First, the key properties of elementary combinations of a few neurons, namely long- and short-term plasticity, spike-timing dependent plasticity (associative plasticity), quantumness and stochastic effects, and their potential computational employment are summarised. Next, several atomic scale device technologies are developed to control electron transport at the atomic level, including single atom implantation for atomic arrays and CMOS quantum dots, single atom memories, Ag2 S and Cu2 S atomic switches, hafnium-based RRAMs, organic material based transistors, and Ge2 Sb2 Te5 (GST) synapses. Each material/method was proved successful in achieving some of the properties observed in real neurons. This paper compares the different methods towards the creation of a new generation of naturally inspired and biophysically meaningful artificial neurons, in order to replace the rigid CMOS based neuromorphic hardware. The most challenging aspect to address appears to be to obtain both the stochastic/quantum behaviour and the associative plasticity, which are currently observed only below and above 20 nm length scale respectively, by employing the same material.